2010
DOI: 10.1016/j.foodchem.2009.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UV-B irradiation on chlorophyll degradation and chlorophyll-degrading enzyme activities in stored broccoli (Brassica oleracea L. Italica Group) florets

Abstract: 22 UV-B irradiation was applied to broccoli florets to investigate its effect on 23 chlorophyll degradation and chlorophyll-degrading enzyme activities in stored broccoli. 24Broccoli florets were irradiated with UV-B doses at 4.4, 8.8 and 13.1 kJ m -2 and then 25 kept at 15 ºC in darkness. We found that a UV-B dose of at least 8.8 kJ m -2 efficiently 26 delayed the decrease of the hue angle value and the contents of chlorophylls a and b. 27Chlorophyllide a and 13 2 -hydroxychlorohyll a gradually decreased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 32 publications
4
59
0
1
Order By: Relevance
“…C13 2 -demethylated catabolites have so far only been identified in the Brassicaceae, and in the past an enzyme termed pheophorbidase has been described, which is capable of hydrolyzing the C13 2 -methylester of Pheide (Suzuki et al 2006). The product of the reaction, C13 2 -carboxyl pyropheophorbide, was shown to spontaneously decarboxylate to pyropheophorbide (Shioi et al 1996b), a proposed product of Chl breakdown mainly found in algae and during post harvest senescence (Ziegler et al 1988;Aiamla-or et al 2010). Pheophorbidase was cloned from Raphanus sativus (Suzuki et al 2006); it is a serine-type esterase and is highly similar to the members of the Arabidopsis methyl esterase (MES) protein family.…”
Section: C13 2 -Methylester Hydrolysismentioning
confidence: 99%
“…C13 2 -demethylated catabolites have so far only been identified in the Brassicaceae, and in the past an enzyme termed pheophorbidase has been described, which is capable of hydrolyzing the C13 2 -methylester of Pheide (Suzuki et al 2006). The product of the reaction, C13 2 -carboxyl pyropheophorbide, was shown to spontaneously decarboxylate to pyropheophorbide (Shioi et al 1996b), a proposed product of Chl breakdown mainly found in algae and during post harvest senescence (Ziegler et al 1988;Aiamla-or et al 2010). Pheophorbidase was cloned from Raphanus sativus (Suzuki et al 2006); it is a serine-type esterase and is highly similar to the members of the Arabidopsis methyl esterase (MES) protein family.…”
Section: C13 2 -Methylester Hydrolysismentioning
confidence: 99%
“…Although there is more research going on the effect of postharvest UV-B treatment on other crops such as, broccoli (Aiamla-or et al, 2010), grapes (Cantos et al, 2000), mushrooms (Roberts et al, 2008), and apples (Hagen et al, 2007), very limited study has been done in case of tomato in the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…In lime fruit, Chl-degrading peroxidase activity increased considerably with the degreening of peel flavedo during storage at 25°C (Kaewsukusaeng et al, 2011). We reported that Chl-degrading peroxidase activity was enhanced concomitantly with the yellowing of florets in stored broccoli (Aiamla-or et al, 2010;Funamoto et al, 2002). In this study, we estimated that Chl-degrading peroxidase activity increased greatly for the first 6 days of storage at 20°C and that the level of naringin, which could act as a substrate of peroxidase, decreased for the first 6 days of storage, suggesting that naringin radical formed by peroxidase could be highly related to Chl degradation of stored Nagato-yuzukichi fruit.…”
Section: Flavonoid and Chlorophyll Analyses By Hplcmentioning
confidence: 95%